Whether monitored anesthesia care is the optimal anesthetic strategy for transcatheter aortic valve implantation surgery? a meta-analysis and systematic review - Lili Xie; Zekun Lang; Ying Liu; Haihong Yue; Qiaoli Chen; Guiyan Tao (BMC Anesthesiology)
Abstract Objectives To explore whether monitored anesthesia care is more beneficial to the outcome of transcatheter aortic valve implantation. Methods The research methodology involved comprehensive searches across major databases, including the Cochrane Library, PubMed, Scopus, and Web of Science, covering the period from January 1, 2010, to March 1, 2024. The aim was to identify trials comparing different anesthetic methods for transcatheter aortic valve implantation. The primary outcomes assessed were mortality and length of hospital stay, while secondary outcomes included common complications such as bleeding, stroke, paravalvular leakage, renal failure, and others. Data synthesis was conducted using risk ratios or standardized mean differences, along with 95% confidence intervals. The study protocol was prospectively registered with PROSPERO (CRD42024507749). Results A total of 35 trials and 45,616 patients were included in this study. The results showed that monitored anesthesia care significantly reduced the patient's risk of death, shortened the patient's length of hospital stay, and also reduced the risk of common complications such as paravalvular leakage (RR, 0.80; 95% CI: 0.72 to 0.88; p < 0.00001; I2 = 0) and stroke (RR, 0.80; 95% CI: 0.65 to 0.99; p = 0.04; I2 = 0). Conclusion Monitored anesthesia care has an absolute advantage in patient survival and effectively shortens the length of hospitalization. In addition, it also reduces the risk of complications such as paravalvular leakage and stroke. Monitoring care under anesthesia plays a vital role during TAVI surgery, not only helping to ensure the smooth progress of the surgery and patient safety, but also promoting the patient's recovery and recovery.